Upaya Meningkatkan Kemampuan Servis Atas Melalui Latihan Lempar Pukul Bola Kertas Dalam Permainan Bola Voli Pada Siswa Kelas VII Smp Negeri 2 Detusoko Ende - Segi, Longginus; Anisa, Novia Dewi; Nara, Oliversius (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
The students of SMP Negeri 2 Detusoko in performing the upper serve are less accurate and hard, even often make mistakes when serving the ball over the net and the ball goes out of the side line of the court. So the learning results of upper serve skills in volleyball are less than optimal and cannot be done well, seen from the student's grades where 16 students of class VII of SMP Negeri 2 Detusoko have not met the grades according to the KKM standard, namely 75.00. This research was conducted at SMP Negeri 2 Detusoko, Nggumbelaka Village, Lepembusu Kelisoke District, Ende Regency. The population in this study were 16 students of class VII of SMP Negeri 2 Detusoko, Nggumbelaka Village, Lepembusu Kelisoke District, Ende Regency, consisting of 8 female students and 8 male students and as well as samples in this study, all were used as research subjects. This research is a type of classroom action research. This research is a type of classroom action research. Based on the implementation of learning and the results of reflection carried out during the implementation of learning cycle II meetings I and II, by obtaining the value of cycle II, the first meeting of the post test obtained a total of 1189.23, a minimum value of 60.71, a maximum value of 85.71 and an average value of 74.32, and the percentage result was 62.5%. While the second meeting of the post test obtained a total of 1328.51, a minimum value of 71.42, a maximum value of 89.28, and an average value of 83.03, and the percentage result was 93.75%. From the results of the data above, the researcher concluded that many seventh grade students of SMP Negeri 2 Detusoko obtained scores above the minimum completeness criteria (KKM).